Application of innovative packaging technologies to manage fungi and mycotoxin contamination in agricultural products: Current status, challenges, and perspectives. (30th July 2022) - Akhila, Plachikkattu Parambil; Sunooj, Kappat Valiyapeediyekkal; Navaf, Muhammed; Aaliya, Basheer; Sudheesh, Cherakkathodi; Sasidharan, Abhilash; Sabu, Sarasan; Mir, Shabir Ahmad; George, Johnsy; Mousavi Khaneghah, Amin
Abstract: The consumer demand for safe, "healthy, " and premium foods, preferably with an extended shelf-life; demand for easy packaging; and choice for more sustainable food packaging have contributed to the development of novel packaging technologies. The application of adequate packaging materials has recently become a major post-harvest challenge concerning the control of fungi and mycotoxin. This review will describe the current antifungal packaging technology involved to prevent the contamination of fungi and mycotoxin, along with the characteristics and mechanism of action in food products. Antifungal packaging has incredible potential in the food packaging sector. The most suitable approach for the safe storage of agricultural produce for farmers is the hermetic packaging technology, which maintains quality while providing a good barrier against fungi and mycotoxin. Furthermore, active antifungal packaging is a viable method for incorporating antifungal agents against pathogenic fungi. Essential oils and organic acid have received more scientific attention due to their increased efficacy against mold growth. Polypeptides, chitosan, and natamycin incorporated in active packaging significantly reduced fungi. Even though nanotechnological advancements in antifungal packaging are promising, safety and regulation issues remain significant concerns. Graphical abstract: Image 1 Highlights: The conventional function of food packaging is evolving in response to shifting market demands. The current antifungal packaging technology to prevent the growth of fungi and mycotoxin was summarized. Antifungal packaging has incredible potential in the food packaging sector. Essential oils and organic acid have received more attention against mold growth.